PENGARUH PELAKSANAAN PROGRAM PELATIHAN DAN PENERAPAN SISTEM MANAJEMEN K3 TERHADAP PRODUKTIVITAS KERJA ANGGOTA PADA DINAS PEMADAM KEBAKARAN KOTA BEKASI - Meta Luvita Sari; Rycha Kuwara Sari (Aliansi : Jurnal Manajemen dan Bisnis, 2021)
This research was conducted to determine whether there is an effect of the implementation of training programs and the application of occupational safety and health management systems on the work productivity of members of the Bekasi city fire department. Based on the results of the research on the Implementation of the Training Program and the Implementation of Occupational Health and Safety Management Systems (K3) on the Work Productivity of Employees at the Bekasi City Fire Department, there is an effect either partially or simultaneously. The conclusion of this study is that the Implementation of the Training Program and Implementation of the Occupational Safety and Health Management System (K3) explains the effect on the Work Productivity of Members at the Bekasi City FireService by 53.8%, while the rest is influenced by other independent variables that are not researched.